Influence of ethanol concentration on the extraction of monacolin K, γ-amino butyric acid (GABA) and antioxidant activity from angkak produced from germinated brown rice as a substrate - Kraboun, Dr.Kitisart (Food and Applied Bioscience Journal, 2019)
The present study estimated the influence of ethanol concentration on the extraction of monacolin K, Y-amino butyric acid (GABA) and antioxidant activity from angkak produced from germinated brown rice as a substrate. The various concentrations (60%, 70%, 80%, and 95%) of ethanol were used as solvents in the extraction of angkak. The monacolin K, GABA and citrinin contents and trolox equivalent antioxidant capacity (TEAC), DPPH radical scavenging activity of angkak were investigated by using various in vitro assays. The pigment extract of angkak extracted with 95% of ethanol concentration led to the highest pigment intensity, monacolin K, GABA and citrinin contents which were 400.92 unit/g substrate, 45.96 mg/kg dry weight, 100.38 mg/kg dry weight and 10.48 µg/kg dry weight, respectively; whereas, the lowest IC50 values of DPPH and ABTS were 0.041 and 0.45 mmol Trolox/mL, respectively.